BAHASA REGISTER PENGAMEN - Nurlaili Dina Hafni (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2017)
Language is a human way of interacting with other humans. Language is the most important sign system in the communication process. The development of language that is in line with the development of human life in modern times shows the changing phenomenon, among others, evidenced by the use of language as a particular tool known as variations of language such as variations of jargon, slang and register. Preliminary language form in the activities of singing in the bus include greetings (general greetings related to time, general greetings meetings, special greetings meetings know, special religious activities). In addition to say hello, another introductory form is to say apologies and express hope. The forms of cover language in busking activities on the bus include greeting (general time regards, general farewell greetings, specialist farewell greetings, special religious greeting activities). In addition to greetings, the singers also thanked, apologized, expressed their wishes, and delivered an appeal in their singing activities.